'Seamless care? Just a list would have helped!' Older people and their carer's experiences of support with medication on discharge home from hospital. (12th August 2011) - Knight, Denise A; Thompson, Diane; Mathie, Elspeth; Dickinson, Angela
Abstract Background Many older people use one or more prescribed medicines on a daily basis. Effective medicines management at hospital discharge can support appropriate use of medicines following discharge and help avoid unnecessary hospital re‐admission. Many people, however, feel they receive insufficient information about medicines on discharge from hospital. Objectives To explore older people and their family carers' experience of hospital discharge in relationship to the organization and management of medicines. Design Qualitative interviews with older people over 75 years old, taking four or more medicines, and their carers, following discharge from hospital in the United Kingdom (UK). Participants completed medication diaries prior to the interview. Setting Interviews took place in the participant's home. Results Nineteen interviews were conducted involving 12 carers and seven older people. Participants were generally not satisfied with the discharge process, particularly concerning perceived delays in discharge. Inadequate explanations about medicines at discharge were commonly reported and led to omission of medicines, incorrect dosage, anxiety and confusion. Poor communication between the hospital and general practitioners or community pharmacists was also evident. Conclusions Despite significant policy recommendations and research in this area, many problems with the management of medicines during hospital discharge were shown, and a lack of partnership was evident between hospital staff and patients/family carers regarding the use of medicines post‐discharge. Improved medicines management during hospital discharge is required to ensure older people take their medications as prescribed and to protect them from the adverse effects of medicines not being taken correctly.